An inclination in Thermal Energy Using Nanoparticles with Casson Liquid Past an Expanding Porous Surface - Umar Nazir (MDPI AG, 2021)
The physical aspects of inclined MHD nanofluid toward a stretching sheet embedded in a porous medium were visualized, which has numerous applications in industry. Two types of nanoparticles, namely copper and aluminum oxide, were used, with water (limiting case of Casson liquid) as the base fluid. Similarity transformations were used to convert the partial differential equations into a set of ordinary differential equations. Closed solutions were found to examine the velocity and temperature profiles. It was observed that an increment in the magnitude of the Hartmann number, solid volume fraction, and velocity slip parameter brought a reduction in the velocity profile, and the opposite behavior was shown for the permeability parameter in <semantics>Cu</semantics>–water and <semantics>Al2O3</semantics>–water nanofluids. The temperature field, local skin friction, and local Nusselt number were further examined. Moreover, the study of <semantics>Cu</semantics> and <semantics>Al2O3</semantics> is useful to boost the efficiency of thermal conductivity and thermal energy in particles. Reduction was captured in the velocity gradient and temperature gradient against changes in the thermal radiation number. The opposite trend was tabulated into motion with respect to the volume fraction number for both cases (<semantics>Cu</semantics>–water and <semantics>Al2O3</semantics>–water).